The Influence of Financial Planning and Self-Control on GenerationZ’s Consumptive Behavior on E-Commerce Platforms - Aswin Akbar; Emelia Rahmadany Putri Gami; Mutawaqil Bilah Tumanggor; Nova Azzahra (Journal of Innovative and Creativity, 2026)
This study examines the influence of financial planning and self-control on consumptive behavior among Generation Z users of e-commerce platforms in Indonesia. The increasing intensity of online shopping, supported by digital payments, promotional strategies, and platform convenience, has encouraged impulsive and excessive purchasing patterns among young consumers. Using a quantitative explanatory approach, data were collected from 150 Indonesian Generation Z respondents aged 17–27 who had made at least one e-commerce purchase within the last six months. The research instrument employed a five-point Likert scale to measure financial planning, self-control, and consumptive behavior. Prior to hypothesis testing, the instrument was evaluated through validity and reliability tests, and the regression model was assessed using classical assumption tests, including normality, multicollinearity, and heteroscedasticity. Multiple linear regression analysis was applied to examine the partial and simultaneous effects of financial planning and self-control on consumptive behavior. The results indicate that financial planning has a negative and significant effect on consumptive behavior, suggesting that individuals who plan budgets, allocate expenditures, and set financial priorities are less likely to engage in unplanned online purchases. Self-control also shows a negative and significant effect, with a stronger influence, highlighting the importance of impulse regulation and resistance to promotional triggers in digital marketplaces. The F-test confirms that financial planning and self-control simultaneously affect consumptive behavior, supporting the proposed research model. The coefficient of determination shows that the model explains a substantial proportion of the variance in consumptive behavior, while the remaining variance may be attributed to factors such as lifestyle, social influence, and platform-driven stimuli. This study contributes to the understanding of Gen Z consumption in Indonesia and provides practical implications for financial education and behavioral interventions to promote responsible e-commerce spending.